Scabies in wildlife animals, pets and humans: a re-emerging zoonosis?. (20th October 2021) - Rubini, S; Zaghi, S; Tazzari, A; Lo Chiano, F; Govoni, G; Cavazzini, M; Taddei, R; Fontana, MC; Barbieri, S; Defilippo, F
Abstract: Background: Scabies or sarcoptic mange is an infestation of the skin caused by the mite Sarcoptes scabiei. Transmission from animals to humans occurs through close contact. The most common symptoms are papules, erythema, excoriations, hyperkeratosis, and hypotrichosis. In the province of Ferrara (Emilia Romagna, Italy) mange is endemic in wild animals, mostly in foxes, which can act as vectors for domestic animals and humans. Methods: From 2012 to 2020, 564 foxes were surveyed within the Wildlife Health Surveillance Re-gional Program, including microscopic examination in cases of skin lesions referable to scabies. In 2018, a domestic dog (10-year border collie, male), frequenting an uncultivated area colonized by foxes and located in the outskirts of Ferrara, showed scabby lesions mainly on the nose, around the eyes and on the back. Results: 11 out of 564 foxes resulted positive (1, 95%), 6 cases out of 38 being in 2018 (15, 8%). The parasite was detected by skin biopsy and direct microscopic examination in the domestic dog. The parasite was transmitted by the dog to the owner and the other two family members. Conclusions: The increased density of dogs and foxes in the Ferrara province, and the attitude of foxes to live near to human settlements, increase the risk of contacts between foxes, domestic animals and humans, even though stray dogs are uncommon. This case illustrates the interdependencies between animal health, human health and environment, a synergy that can enable exacerbation of diseases of zoonotic origin as highlighted by the One Health concept. It is therefore important to increase the investigation on paths as well as vectors of diseases and to find collaborative, multi-sectorial and transversal approaches to ensure quality health outcomes. The control of the disease requires an appropriate monitoring of dogs' health being skin lesions in both, humans and animals, very similar to allergic dermatitis, which can delay the proper diagnosis of the disease. Key messages: Sarcoptic mange is a zoonosis still present in Emilia Romagna, Italy. The One Health approach is key to control the cycle of the zoonotic sarcoptic mange.